2015
DOI: 10.1080/02602938.2015.1030588
|View full text |Cite
|
Sign up to set email alerts
|

Improving the effectiveness of feedback by use of assessed reflections and withholding of grades

Abstract: We wished to improve levels of student engagement with feedback within the context of our postgraduate masters-level programme, and therefore evaluated the use of two interventions: assessed reflections on feedback, and grade-withholding. In questionnaires students reported more engagement with feedback after the interventions, with 77% in favour of using reflections, though only 57% favoured grade-withholding, with feelings of frustration and anxiety about the grade cited as factors. Overall class grades impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Encouragingly though, Zimbardi et al () found that only a small percentage of students appeared to be accessing feedback files merely for their mark (only 6% opened reports for less than 1 minute), which suggests that once students access feedback files they may be more likely to engage with feedback as well. “Adaptive release,” where feedback is released first followed by marks at a later date has also been suggested as a mechanism to enhance student access to feedback (Irwin et al , ); however, mark withholding can lead to student resentment and anxiety (Jackson & Marks, ; Parker & Winstone, ; Parkin et al , ). Incorporating grades into feedback files in LMS could provide a simple alternative to increase engagement with feedback while minimising student frustration regarding the availability of their marks.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly though, Zimbardi et al () found that only a small percentage of students appeared to be accessing feedback files merely for their mark (only 6% opened reports for less than 1 minute), which suggests that once students access feedback files they may be more likely to engage with feedback as well. “Adaptive release,” where feedback is released first followed by marks at a later date has also been suggested as a mechanism to enhance student access to feedback (Irwin et al , ); however, mark withholding can lead to student resentment and anxiety (Jackson & Marks, ; Parker & Winstone, ; Parkin et al , ). Incorporating grades into feedback files in LMS could provide a simple alternative to increase engagement with feedback while minimising student frustration regarding the availability of their marks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are two main obstacles to formative assessment that most studies in this field describe, even in non-Asian formative assessment studies, its time-consuming nature and demanding workload (Akom, 2010;Asghar, 2009;Falk, 2011;Jackson & Marks, 2015;OECD, 2005). When implementing formative assessment in the classroom, teachers were required to do additional work (e.g., eliciting student learning information, comparing learning outcomes, giving feedback, adjusting instructions) in order to satisfy the learning needs of individual students.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because students tend to focus on grades and want to know their grades, temporary mark withholding could be met with skepticism (Smith & Gorard, 2005). However, openly discussing the rationale behind this approach, managing student expectations, and designing short activities (e.g., in the form of written reflection statements or answering questions about the obtained feedback) can enhance student buy-in into temporary mark withholding as a valuable approach (see Jackson & Marks, 2016;Sendziuk, 2010). A blog post by Louden (2017) outlines a plan on how to implement temporary mark withholding and specifically points to the importance of giving agency to students during the feedback phase by providing them with opportunities to respond to written feedback before receiving their marks.…”
Section: Discussionmentioning
confidence: 99%
“…The current research explores the triangular interaction between student characteristics, their cognitive processes, and a feedback intervention. More specifically, we focus on the tendency of students to prioritize grades at the expense of processing the written comments and feedback (Jackson & Marks, 2016) and investigate temporary mark withholding-the systematic delaying of marks release in favor of providing feedback and comments first-as a potential feedback intervention.…”
mentioning
confidence: 99%